THE KNOWLEDGE-SHARING CULTURE IN AN OPERATIONAL EXCELLENCE PLANT AS COMPETITIVE ADVANTAGE FOR FORWARD-THINKING ORGANIZATIONS - Lechner, Horst J. (PEOPLE: International Journal of Social Sciences, 2023)
Although knowledge sharing has been discussed quite a bit in the literature, the mediating and moderating mechanisms that influence team members in knowledge sharing to move from connecting with each other to building social capital and consequently engaging in knowledge sharing are still largely unexplored. This paper aims to shed light on the currently poorly understood knowledge flow of project managers across the value chain in the food-mass-production industry and to show the significance of competitive intelligence for plants in in the mass-production industry, the influence of competitive intelligence on strategic decisions, especially on positioning decisions, and the extent to which this process is influenced by the development of external influences and framework conditions. The findings are based on a literature review and the author’s five years of action research in the foot-packaging industry, supplemented by his annual audits. Unfortunately, literature examining the influence of organizational culture on knowledge sharing behaviours is not widely available. Thus, this paper is a methodological-theoretical attempt to review the literature on knowledge sharing examples, and thoroughly parses the knowledge gaps and potential pitfalls of misunderstanding. Unfortunately, literature examining the influence of organizational culture on knowledge sharing behaviours is not widely available. The results of this paper enrich the theory of organizational culture and knowledge management and help policy makers in providing measures to develop knowledge sharing behaviours.